DISTRIBUSI PENGELUARAN KONSUMSI RUMAHTANGGA PETANI KARET POLA EKS UPP TCSDP DAN POLA SWADAYA DI DESA KOTO DAMAI KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR - Resi Zilviana; Eliza Eliza; Suardi Tarumun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aimed to analyze the distribution of household consumption expenditure, household wealth and household consumption expenditure comparison of ex- UPP TCSDP rubber farmers and Independent Smallholder in Koto Damai  village, midle-left of Kampar district Kampar regency. The research was conducted by survey method. Data were collected 30 samples of rubber farmers ex UPP TCSDP by using purposive sampling method and 20 samples ofindependently smallholderby using census method. The results showed that total household consumption expenditure ex UPP TCSDP rubber farmers was Rp 2,421,982 / RT / Month and the total household consumption expenditure independent smallholder amounted to Rp 1,637,013/Rt/Month. Household welfare ex UPP TCSDP rubber farmers and independent smallholderon approach of using proverty line including not poor category because household income in a month is above the poverty line of Kampar Regency 336.681. Based on 14 indicators of the fulfillment of the basic needs, 100 percent ex UPP TCSDP rubber farmers is  prosperous and 95 percent independent smallholder  in the category prosperous meets 1-3 indicators are in bad conditionand 5 percent in almost prosperous category meets 4-8 indicator bad condition.The results also show that there are differences in household consumption expenditure ex UPP TCSDPrubber farmers and independent smallholder because t count equal to 2,515 bigger than t table of 2.011. Keywords : rubber farmers, consumption expenditure, welfare